Mr. Universe [videorecording (DVD)] - Gaffigan, Jim (Image Entertainment, 2015)
Jim Gaffigan performs live stand-up comedy. He answers such questions as why whales are fat; the effect of hotel rooms on behavior; fast food; etc.